Desarrollo de una aplicación móvil para el monitoreo de la fonometría vegetativa del maíz amarillo, en la sierra central ecuatoriana. - Cando Sarango, Diana Aracely (2021)
Agriculture can be described as the production, processing, sale, and disposal of crops and livestock. This is modern knowledge because in its time it was considered a special time for the consumption of vegetables. Agriculture plays an important role in the country's economy, in addition to providing us with food and natural resources, but also providing employment opportunities for many people. Currently mobile applications are applied in all fields, one of them agriculture, many of these applications are intended to improve crop production, some farmers use them and have benefited from technology. This research proposes to carry out a study on the phenometry of the maize plant in the central highlands in the province of Tungurahua, which is specifically focused on the measurement of the length and diameter of the maize stem in a digital image.